Answer:
do u mind helping me for school ?
if so check my latest questions pls ty
Step-by-step explanation:
Answer:
(i) A truth table shows how the truth or falsity of a compound statement depends on the truth or falsity of the simple statements from which it's constructed.
Since A ∧ B (the symbol ∧ means A and B) is true only when both A and B are true, its negation A NAND B is true as long as one of A or B is false.
Since A ∨ B (the symbol ∨ means A or B) is true when one of A or B is true, its negation A NOR B is only true when both A and B are false.
Below are the truth tables for NAND and NOR connectives.
(ii) To show that (A NAND B)∨(A NOR B) is equivalent to (A NAND B) we build the truth table.
Since the last column (A NAND B)∨(A NOR B) is equal to (A NAND B) it follows that the statements are equivalent.
(iii) To show that (A NAND B)∧(A NOR B) is equivalent to (A NOR B) we build the truth table.
Since the last column (A NAND B)∧(A NOR B) is equal to (A NOR B) it follows that the statements are equivalent.
Option A
<u>Answer:
</u>
The value of x in the equation 2(x - 3) + 5x = 5(2x + 6) is -12
<u>Solution:
</u>
From question given that
2(x - 3) + 5x = 5(2x + 6)
Open the brackets,
2x – 6 + 5x = 10x + 30
Rewrite the above equation,
2x + 5x – 6 = 10x + 30
On simplifying the above equation, we get
7x – 6 = 10x + 30
Now adding 6 on both sides,
7x – 6 + 6 =10x + 30 + 6
7x = 10x + 36
On subtracting 10x on both sides,
7x - 10x = 10x + 36 - 10x
-3x = 36
On dividing -3 on both sides,
x = -12
Hence on simplifying 2(x - 3) + 5x = 5(2x + 6) we get value of x is -12. Hence Option (A) is correct.
Answer: 
You can write this as (-infinity, 7) if you aren't able to use the infinity symbol.
====================================================
Explanation:
Think of x < 7 as writing 
So x is between negative infinity and 7, excluding both endpoints.
To write
in interval notation, we write
The curved parenthesis tell us to exclude the endpoint.